COVID-19, camping and construal level theory. Issue 20 (18th October 2021) - Craig, Christopher A.; Ma, Siyao; Karabas, Ismail
ABSTRACT: This study explores the impact of COVID-19 on travellers' future recreational vehicle, cabin and tent camping decisions extending the construal level theory. Findings suggest that camping consideration due to COVID-19 is significantly related to understanding about time and distance of travel and dependent on pandemic scale.